Investigation of amoxicillin removal from aqueous solution by Fenton and photocatalytic oxidation processes - Koyuncu Turkay, Gamze; Kumbur, Halil (Kuwait Journal of Science, 2019)
This study aimed to investigate the removal of amoxicillin (AMO) antibiotic and chemical oxygen demand (COD) by Fenton (Fe2+/H2O2) and photocatalytic (UV-A/TiO2) oxidation processes in aqueous solution. In experiments, pH, antibiotic, Fe2+, H2O2, TiO2 concentrations and reaction time parameters were examined. In Fenton process, the removal efficiencies of initial AMO and COD concentrations were 83% and 66%, respectively. Fe2+/H2O2 molar ratio was determined as 1/15. In Photocatalytic process, AMO and COD removal efficiencies were 62% and 52%, respectively. The results indicated that these two processes may enhance the rate of AMO removal in polluted water and could be used as a preliminary treatment, alternative to existing treatment systems.